Making religious buildings more accessible: The case of mosques in Abu Dhabi’s and Dubai’s neighborhoods - Khaled Alawadi; Nour Alkhaja; Mariam Alazab Alhadhrami; Sara Omar Mustafa (Journal of Transport and Land Use)
More than a house of worship, religious buildings have a critical and authoritative role in the social and political life of people. Yet, such places of divine and spirit have received limited attention in transportation and urban planning research. This research evaluates accessibility to one kind of religious institution: mosques. The article studies the ease of access to mosques at walkable distances of 400 m and 800 m radii in twelve selected neighborhoods in Abu Dhabi and Dubai. Analysis uses the gravity metric under two network scenarios: streets only, and the combined network of streets and alleys. Gravity values demonstrate three types of accessibility to mosques: plots without access, plots with minimum access to one mosque, and plots with choice access to more than one mosque. Findings show neighborhoods have experienced an erratic decrease in accessibility to mosques. In both cities, percentages of plots with an overall accessibility to mosques, (sum of both minimum and choice), were higher in the pre- and-early-suburban phases. With the inclusion of alleyways, the overall accessibility percentages increased in many cases. The study reveals that good pedestrian accessibility results from an effective interplay between street design, plot densities, network intersection density, strategic placement of alleys, and mosques’ ratio and spatial distribution.